CT-guided laser probe for ablation of brain tumors - Abdolhadi Daneshi; Mousa Taghipour; Sadegh Izadi; Reza Mollahossaini; Hossain Ghaleh-Noyi; Mehdi Ghaffari; Reza Alizadeh; Reza Ahadi (Basic and Clinical Neuroscience, 2010)
Abstract  In this study, 22 patients (15-75 years old) were selected and transferred to CT scan for tumor ablation. For ablations, after prep and drep under the local anesthesia and mild sedation in proper position, small incision made and special needle inserted and guided by proper direction to the core of the tumor. Then, laser probe inserted through the needle and laser energy delivered. Although we have not a good prognosis in metastatic tumors but post-operative follow up and brain CT scan established the effect of laser on resection and evaporation and diminution of mass effect in tumor lesions.